2022
DOI: 10.3390/brainsci12101294
|View full text |Cite
|
Sign up to set email alerts
|

Human-in-the-Loop Optimization of Transcranial Electrical Stimulation at the Point of Care: A Computational Perspective

Abstract: Individual differences in the responsiveness of the brain to transcranial electrical stimulation (tES) are increasingly demonstrated by the large variability in the effects of tES. Anatomically detailed computational brain models have been developed to address this variability; however, static brain models are not “realistic” in accounting for the dynamic state of the brain. Therefore, human-in-the-loop optimization at the point of care is proposed in this perspective article based on systems analysis of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(77 citation statements)
references
References 95 publications
(189 reference statements)
0
17
0
Order By: Relevance
“…In our prior study (6), we found from modal analysis and a case study in a healthy human that the "optimal" oscillatory frequency was close to 1 Hz, meriting mechanistic investigation with respect to astrocytes and interstitial potassium. In this study, short-term (<150 s) acute tES can affect the vasculature (41) for immediate control of blood vessel response using model predictive control (MPC) (6). MPC uses an internal model of the interaction of cortical activity, local metabolic factors, and the vascular response to make predictions of the system behavior, considering neurovascular dynamics over a predefined prediction horizon, to optimize tES control actions.…”
Section: Pathway : Perturbation Of Perivascular Potassium Concentrati...mentioning
confidence: 99%
See 4 more Smart Citations
“…In our prior study (6), we found from modal analysis and a case study in a healthy human that the "optimal" oscillatory frequency was close to 1 Hz, meriting mechanistic investigation with respect to astrocytes and interstitial potassium. In this study, short-term (<150 s) acute tES can affect the vasculature (41) for immediate control of blood vessel response using model predictive control (MPC) (6). MPC uses an internal model of the interaction of cortical activity, local metabolic factors, and the vascular response to make predictions of the system behavior, considering neurovascular dynamics over a predefined prediction horizon, to optimize tES control actions.…”
Section: Pathway : Perturbation Of Perivascular Potassium Concentrati...mentioning
confidence: 99%
“…Here, we postulate that the extracellular space, including the extracellular matrix plays a crucial role during online modulation by tES, which is relevant in the optimisation of the tES dose (6). For example, tES modulation of the permeability of the blood-brain barrier (11) can change the substance transport (12) including glucose that can modulate neuronal excitability (13) and neurovascular coupling [for a given insulin action (14,15)].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations